2019
DOI: 10.3390/app9142931
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Robot Exploration Based on Multi-Objective Grey Wolf Optimizer

Abstract: In this paper, we used multi-objective optimization in the exploration of unknown space. Exploration is the process of generating models of environments from sensor data. The goal of the exploration is to create a finite map of indoor space. It is common practice in mobile robotics to consider the exploration as a single-objective problem, which is to maximize a search of uncertainty. In this study, we proposed a new methodology of exploration with two conflicting objectives: to search for a new place and to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 48 publications
0
14
0
1
Order By: Relevance
“…In the authors' previous studies [33], [34], coordinated multi-robot exploration and waypoint selection concepts [35], [36] using GWO were introduced in the probabilistic occupancy grid map. The optimization strategies in both studies showed one common drawback of such stochastic optimization methods, which is the aborted simulation runs.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…In the authors' previous studies [33], [34], coordinated multi-robot exploration and waypoint selection concepts [35], [36] using GWO were introduced in the probabilistic occupancy grid map. The optimization strategies in both studies showed one common drawback of such stochastic optimization methods, which is the aborted simulation runs.…”
Section: Related Workmentioning
confidence: 99%
“…In the current study, a new concept for the GWO exploration algorithm is presented, which differs from the previous ones [33], [34], that is, the occupancy probabilities of cells are not applied in this study. Also, the previous studies used eight neighbor points around the robot as candidates for the next robot position.…”
Section: Algorithm 1 Grey Wolfmentioning
confidence: 99%
“…It tries to discover unknown areas of the environment to add them to the map so that the robot can have a more complete knowledge of the surroundings. Kamalova et al [3] develop a method to explore unknown indoor environments, with the purpose of building a model of them. They approach the problem as a multiple-objective exploration, using the Multi-Objective Grey Wolf Optimizer (MOGWO) algorithm, which employs static waypoints in the process, promoting the efficient exploration of indoor environments.…”
Section: Map Building and Localization Of Mobile Robotsmentioning
confidence: 99%
“…Bio-inspired techniques are most popular, and researchers are implementing them solving path planning problem for AGV or mobile robots [1]. The popular bio-inspired algorithms are based on the living creature behavior which include birds, bees, ants, whale, bat, fish, wolf [2][3][4][5][6][7][8]. Randomly exploring tree algorithm with pure pursuit controller can be found in [9].…”
Section: Introductionmentioning
confidence: 99%